Challenges to the provision of home care and support for people with severe mental illness: Experiences and perspectives of patients, caregivers, and healthcare providers in Dar es Salaam, Tanzania. - Joel Seme Ambikile; Masunga K Iseselo (Public Library of Science (PLoS), 2023)
A balance between hospital-based and community-based services is needed to effectively provide mental health services for people with mental illness. As an essential part of community mental health services, home-based care plays an important role in meeting patients' needs, and should, therefore, be appropriately provided. To achieve this, there is a need to understand the challenges faced and take relevant actions to address them. This study aimed to explore challenges to home care and support for people with mental illness in Temeke district, Dar es Salaam. We used a descriptive qualitative study approach to explore challenges to home care and support for people with mental illness among patients, their caregivers, and healthcare providers. The purposeful sampling method was used to recruit participants at Temeke hospital, data was collected using in-depth interviews and focus group discussions, and analysis was performed using a content analysis framework. Four main themes highlighting challenges encountered in the provision of home care and support for individuals with mental illness were revealed. They include poor understanding of mental illness, abandonment of patients' care responsibilities, disputes over preferred treatment, and lack of outreach services for mental health. Participants also provided suggestions to improve home care and support for people with mental illness. Home care for people with mental illness is affected by poor knowledge of the mental illness, social stigma, and lack of outreach visits. There is a need for the provision of health education regarding mental illness, stigma reduction programs, and funding and prioritization for outreach home visits to improve home care and support for people with mental illness. Further research is needed to determine the magnitude of these challenges and factors that can facilitate the provision of support in similar settings.